Experiments in rabbits suggest Nierembergia veitchii as a cause of enzootic calcinosis in sheep of Rio Grande do Sul Brazil - Riet-Correa, Franklin; Mendez, Maria Del Carmen; Schild, Ana Lúcia; Santos, Edgar Cardoso dos; Scarsi, Roberto Mário (Pesquisa Agropecuaria Brasileira, 2014)
Several plants mixed with ration were given to rabbits, in order to determine the etiology of enzootic calcinosis in sheep of Rio Grande do Sul. Commercial food with 50% of Nierembergia veitchii Hook (Solanaceae family) added, when given to four rabbits produced soft tissue calcification, inhibition of the osteocytic osteolysis, osteopetrosis and osteonecrosis. Neither macroscopic nor histologic evidences of calcinosis were observed in fifteen rabbits fed with other plants, as well as six rabbits from the control group. It is demonstrated that N. veitchii has calcinogenic properties in rabbits, which seems to indicate that it is associated to the production of enzootic calcinosis in sheep.